Capacidad. Discapacidad. Incapacidad. Incapacitación - Fernández de Buján, Antonio (Revista de Derecho de la UNED (RDUNED), 2011)
La elaboración de los conceptos de capacidad jurídica y capacidad de obrar tiene su origen en la Pandectística alemana y en la tradición romanística. La relación entre discapacidad e incapacidad es poliédrica, si bien cabe decir que la discapacidad es una situación administrativa y la incapacidad un estado civil. La Convención Internacional de 2006 sobre los Derechos de las personas con discapacidad, ratificada por España en 2008, supone en cambio de paradigma que obliga a adaptar la legislación española al respecto. The elaboration of the concepts of juridical capacity and legal capacity has its origin in German Pandectists and the Roman law tradition. The relation between disability and incapacity is polyhedral, although it can be said that disability is an administrative situation and incapacity is a civil state. The 2006 International Convention on rights of handicapped people, ratified by Spain in 2008, entails a change in the paradigm that will force a modification and adaptation of Spanish legislation on the subject.